APPLICATION OF THE SIMULATION MODEL IN TEACHING PROCESS IN THE CONTEXT OF THE DEVELOPMENT OF INFORMATION THINKING - SEDLÁČEK, Michal (Trends in education, 2022)
The paper deals with a demonstration of the possibility of using a modeling and simulation tool in teaching computer science. Simul8 software was chosen as the default, which is used to model processes based on discrete event simulation and allows the creation of a visual simulation model and event animation. An example is the application of modeling in teaching in the form of a visual demonstration tool with a high motivational potential for students. The paper demonstrates the specific steps in the process of creating a simulation model usable in teaching and focused on the development of computer thinking.
Keywords: process modeling; simulation software; digital literacy; informatics thinking; demonstration means of teaching